Synthesis, characterization and thermally induced structural transformation of Au-C70 nanocomposite thin films. (August 2017) - Singhal, Rahul; Vishnoi, Ritu; Sharma, Pooja; Sharma, G.D.; Chand, S.; Kanjilal, D.; Pivin, J.C.
Abstract: Au-C70 nanocomposite thin films are deposited using thermal co-evaporation technique. Low atomic concentration of Au (∼3%) are used to avoid any deterioration of the properties of fullerene C70 when used with Au. These thin films are annealed in inert atmosphere at different temperatures for 30 min in order to promote the formation of nanocomposite material. Both the Au nanoparticles and fullerene C70 matrix are evolved by thermal treatment. Spherical shaped Au nanoparticles with a diameter of 3.8 ± 0.1 nm are clearly observed in the TEM images at 350 °C. The characteristic D and G bands of amorphous carbon are evidenced by Raman scattering spectroscopy in the film annealed at 350 °C. The surface plasmon resonance (SPR) absorption band of Au nanoparticles in carbon is obtained at 565 nm after treatment at 300 °C and it is blue shifted to 549 nm for the sample annealed at 350 °C. Graphical abstract: Highlights: Au-C70 nanocomposite is synthesized using thermal co-evaporation technique. Investigations on thermal induced structural transformation of nanocomposite films. Spherical shaped Au nanoparticles in carbon matrix are seen at 350 °C. SPR band is blue shifted for the sample annealed at 350 °C. SPR position and width is dependent on both, metal and matrix.